A DETECÇÃO DE SINAIS E SINTOMAS DA VIOLÊNCIA NA FASE DIAGNÓSTICA DA PSICOTERAPIA BREVE - Maia, Sílvia Suely de Souza (2008)
The present work seeks to investigate, the interferences of domestic violence in the diagnostic phase that precedes the brief psychotherapy, and her importance in the clinical image showed for the patient, if the violence was verbalize by the patient and the conditions how it was captivate for therapist and to lead in consideration in the diagnostic diagnostic phase of Childish Brief Psychotherapy. The sample of the present investigation to consist of 29 patient of Childish Brief Psychotherapy. The work consist from one Analysis of 03 or 04 initials interviews with constitute the diagnostic phase of the Brief Psychotherapy, accomplished for two judges. It was prove the presence of domestic violence into 24 of the 29 cases analyzed, that corresponds at 83% of the whole of patient. The domestic violence was considered significant into 13, of the 24 cases that was to evidence occurrence of domestic violence, that correspond to 54% of the whole cases of domestic violence. Of the 13 cases that the domestic violence was significant, about 54% it was include in the psychodynamic comprehension of the protest, by the therapist. The insert og domestic violence in the focus was observed in only 2 cases, that correspond to 15% of the cases that the domestic violence was significant. The results obtained were debate on the shine of the biography and was related with the question of the collusion of the family and the proper therapist. This collusion dificult the inclusion of violence in the protest by family, and otherwise, her investigation in the comprehension of the psychodynsmic of the protest, from the therapist. Such resistences to struggle with violence have hers refex in the evolution of the process psychotherapeutic.(AU)